Global media : the television revolution in Asia - White, James D. (James Daniel) (East Asia (New York, N.Y.), 2005)
This book is about the processes of globalization, demonstrated through a comparative study of three television case histories in Asia. Also illustrated are different approaches to providing television services in the world: public service (NHK in Japan), state (CCTV in China) and commercial (STAR TV, based in Hong Kong). Through its focus, Global Media addresses a considerable lacuna in the media studies literature, which tends to have a heavy Western bias. It provides an original addition to the literature on globalization, which is often abstract and anecdotal, in additio.